Physicochemical and Functional Properties of Starch from Breadnut (Artocarpus communis G.Forst) Seed - Sukatiningsih, Sukatiningsih (Jurnal Teknologi Pertanian, 2005)
Basic information on chemical composition of Indonesian breadnut seed flour and physicochemical as well functional properties of its starch is scarce and therefore the product is still underutilized in industry. The objective of this research is to study the chemical composition of breadnut seed and to evaluate some of the physicochemical and functional properties of its starch for food processing. The starch of the breadnut seed was extracted with brine at a various salt concentration, i.e. 0%, 0.03%, and 0.1%. (w/v). The results indicated that the dried seed of breadnut with moisture content of 10.835% was composed of protein (8.843%), 5.599% lipid, ash (1.499 %), 8.197 % crude fiber, and carbohydrate (64.965 %). It also contains phenols at a level of 0.061 %. The concentration of salt increased the yield, degree of whittenes, gelatinization temperature, paste viscosity, swelling capacity increased with salt concentration, but the amylose content was reduced. The starch granule was not affected by the salt concentration. Â  Key words : breadnut seed, starch, physicochemical properties.